El Niño and human health - R. Sari Kovats (The World Health Organization, 2000)
The El Niño-Southern Oscillation (ENSO) is the best known example of quasi-periodic natural climate variability on the interannual time scale. It comprises changes in sea temperature in the Pacific Ocean (El Niño) and changes in atmospheric pressure across the Pacific Basin (the Southern Oscillation), together with resultant effects on world weather. El Niño events occur at intervals of 2-7 years. In certain countries around the Pacific and beyond, El Niño is associated with extreme weather conditions that can cause floods and drought. Globally it is linked to an increased impact of natural disasters. There is evidence that ENSO is associated with a heightened risk of certain vector-borne diseases in specific geographical areas where weather patterns are linked with the ENSO cycle and disease control is limited. This is particularly true for malaria, but associations are also suggested in respect of epidemics of other mosquito-borne and rodent-borne diseases that can be triggered by extreme weather conditions. Seasonal climate forecasts, predicting the likelihood of weather patterns several months in advance, can be used to provide early indicators of epidemic risk, particularly for malaria. Interdisciplinary research and cooperation are required in order to reduce vulnerability to climate variability and weather extremes.